Increasing HIV-1 pretreatment drug resistance among antiretroviral-naïve adults initiating treatment between 2006 and 2014 in Nairobi, Kenya. (19th June 2016) - Chung, Michael H.; Silverman, Rachel; Beck, Ingrid A.; Yatich, Nelly; Dross, Sandra; McKernan-Mullin, Jennifer; Bii, Stephen; Tapia, Kenneth; Stern, Joshua; Chohan, Bhavna; Sakr, Samah R.; Kiarie, James N.; et al.
Abstract : Antiretroviral-naïve adults initiating antiretroviral therapy in Nairobi, Kenya were tested for HIV-1 drug resistance at codons K103N, Y181C, G190A, M184V, and K65R using an oligonucleotide ligation assay. Prevalence of pretreatment drug resistance increased from 3.89% in 2006 to 10.93% in 2014 ( P < 0.001), and 95% of those with resistance had at least one nonnucleoside reverse transcriptase inhibitor mutation. Resistance to tenofovir (K65R) was found in 2014 but not in 2006.